The effect of the fraction of used tobacco raw materials on the quality of shisha tobacco - N. N. Bubnova; E. A. Bubnov; S. V. Gvozdetskaya (Новые технологии)
Due to the rapid growth in the production and consumption of shisha tobacco in the Russian Federation, it has become necessary to improve the technology using optimal ingredient composition in order to create a high-quality and safe tobacco product. The aim of the research is to improve the technology of manufacturing shisha tobacco based on the optimization of its ingredient composition; to study the influence of the fractional composition of raw tobacco on its quality indicators. Fractional composition of raw tobacco in the production of shisha tobacco, as well as for other tobacco products, is important and affects its quality characteristics. Virginia and Burley tobaccos of the American type are the most demanded ones in the manufacture of shisha tobacco [1]. Sometimes oriental-type tobaccos are used in the bag, which are distinguished by high taste and aromatic qualities. Due to the fact that recently there has been an increase in the demand for Doha Arabian tobacco raw material (this tobacco is known as a high-quality product with a high strength and a pleasant, full and harmonious taste), the idea has arisen to manufacture prototypes of shisha mixtures in which Doha tobacco is used [2]. The article presents the research results: to determine the optimal ingredient composition of hookah tobacco; to study the optimal fractional composition of raw tobacco of various types. As a result of the research the chemical composition of raw tobacco of various types has been analyzed, the tasting and organoleptic evaluation of the prototypes carried out and the tobacco raw material most suitable for the production of shisha tobacco determined; the nicotine content in the condensate of prototypes of shisha mixtures with different fractions of raw tobacco determined; the optimal fractional composition for various types of tobacco raw materials, necessary for the production of a quality product determined.